Botos Lagoon, Poás Volcano National Park, Costa Rica – Consumer drones in professional research - Godfrey, Ian (2023)
The International Union of Geological Sciences designated the Poás Volcano National Park in Costa Rica one of the top 100 sites for geological importance in the world. This was announced on the World Geological Heritage list which includes sites from 56 additional countries. The Poás Volcano stands out next to Mount Everest in Nepal, the Grand Canyon in the United States and the caldera of Santorini in Greece. The Poás Volcano National Park is an active volcanic crater visible from the crater rim and is one of the most visited National Parks in Costa Rica. Consumer drones were used at the Poás Volcano National Park in particular at the Botos Lagoon for observational research and environmental monitoring for several conservational applications assisted by the use of drones. UAS have been periodically used by the Laboratory of Atmospheric Chemistry Universidad Nacional LAQAT-UNA for monitoring the Botos Lagoon for geological fluctuations. Economically priced drone systems have now become common pieces of field work equipment for volcanologists. Most importantly they offer the opportunity to access dangerous difficult to reach areas of the volcano and allow for the collection of data on the otherwise inaccessible areas. By compiling all of this data together in a collective analytical survey of the Poás Volcano including the Botos Lagoon located in the prehistorical dormant crater, much valuable data can be brought to the scientific community for increased understanding of the Poás Volcano National Park and its importance to the nation.